Effect of aquapuncture on postoperative analgesia after ovariohysterectomy in dogs - Luna, Stelio Pacca Loureiro [UNESP]; Kelawala, Nareshkumar Hasmukhlal; Da Maia Lima, Alfredo Feio [UNESP]; Saarto, Erja Elina; Restitutti, Flavia Corte; De Oliveira Figueiredo Da Silva, Nuno Emanuel [UNESP] (Universidade Estadual de Londrina, 2015)
Aquapuncture (AqP) consists of a water or saline solution injection into acupoints. This study aimed to evaluate the effect of aquapuncture on post-operative analgesia in bitches submitted to elective ovariohysterectomy (OHE). The study was prospective, randomised, and blinded for pain assessment. Sixteen dogs were randomly distributed in two groups of eight animals each. All animals were sedated with 0.05 mg kg-1 of acepromazine intramuscularly (IM), 30 minutes prior to induction of anaesthesia with propofol and maintenance with isoflurane. Eight animals underwent bilateral acupoint injection with 0.1 ml of 0.9% saline (AqP) at Gall Bladder 34, Stomach 36, Liver 3 and Spleen 6 acupoints 15 minutes after sedation. Pain score was investigated after 0.5, 1, 2, 5, 8 and 24 hours post-operatively and was compared with a control untreated group of eight animals. Morphine, at 0.5 mg kg-1 IM, was administered when the numerical rating scale was above 33% of the maximum value, in order to control post-operative pain in both groups. There were no differences in cardiorespiratory variables and pain and sedation scores between the groups. Seven (87.5%) animals from the control group required rescue analgesia at the first two postoperative hours and five (62.5%) animals treated with AqP required rescue analgesia, however, only one (12.5%) animal was treated at the first two hours and the remaining animals were treated from 5 hours after surgery. Aquapuncture produced residual analgesia up to 5 h after surgery and may be an option for post-operative analgesia in bitches undergoing OHE, providing that pain is assessed and rescue analgesia administered if necessary.
Keywords: Acupuncture; Morphine; Pain; Surgery